The Effects of A Social Relationship Program on The Loneliness of Older - แก้วพิจิตร อุทัยวรรณ; สมประเสริฐ ชมชื่น; กรรมบุตร จีราภรณ์ (Journal of The Royal Thai Army Nurses, 2018)
This quasi-experimental research using a two-group pretest-posttest design aimed to examine the effects of a social relationship program on the loneliness of the elderly. The subjects of this research were 62 elderly persons aged 60 and over, who met the inclusion criteria. The subjects were randomly assigned to an experimental group (n = 31) and control group (n = 31). The experimental group participated in an eight - week social relationship program that was developed based on the concepts of social support and social networks, while the control group received regular care activities. The research instruments were the social group program and the loneliness scale. The content validity of the social relationship program was examined by three experts. The Cronbach’s alpha coefficient for the loneliness scale was .70. The data were analyzed using descriptive statistics, dependent t-test, and independent t-test. The results of the study were as follows = .1) After participating in the social relationship program the mean score for the loneliness of the experimental group (M = 28.13, SD = 5.96) was lower than the pretest score (M = 34.23, SD = 7.19) at a statistical significance (t = 16.39, p<.001). 2) The mean difference scores for the loneliness of the experimental group between before and after participating in the social relationship program ( = 6.10, SD = 2.07) was higher than that of the control group receiving normal regular care ( = .16, SD = 1.04) at a statistical significance (t = 15.045, p<.001).